Early Warning System for Dengue Hemorrhagic Fever (DHF) Epidemics in Makassar - Halmar Halide; Rais Rais; Peter Ridd (Jurnal Matematika & Sains, 2011)
A three-month in advance warning system for upcoming DHF epidemics is developed. The system uses a simple predictive regression model based on past and present DHF cases, climate and meteorological observations as inputs to predict future DHF cases. Using Peirce score as a measure of prediction skill, the model only successfully predicts a moderately-severe epidemic at lead times of up to 6 months. Another model uses a discriminant method is also developed. This model gives much higher skill score and longer lead times than that of the regression model. The economic benefit of using the discriminant models forecast to protect a family from an epidemic is also demonstrated. It is shown that families who are implementing such a prediction into their decision making process gain more benefit than those with un-informed decisions.Â